RP-HPLC Method for Detection and Quantification of Residual Fluoroquinolones in Buffalo Meat - Kalpana, S.; Muthukumar , M. (Journal of Meat Science, 2019)
A reverse-phase liquid chromatographic method for simultaneous quantification of enrofloxacin and its active metabolite ciprofloxacin  in buffalo meat matrix is described. The method entails simple liquid-liquid extraction of meat samples. After extraction of the meat  samples for the two fluoroquinolones, the analysis of the drugs was carried out using a reverse phase C18 column at an oven tempera ture of 40ºC. The chromatographic separation was accomplished with mobile phase consisting of 0.1% aqueous formic acid and 0.1%  formic acid in acetonitrile (80:20, v/v) in an isocratic elution mode. The flow rate of the mobile phase was maintained at 1.2 ml/min and  injection volume was 20 µl. A fluorescent detector was operated at an excitation and emission wavelength of 280 and 450 nm. The assay  was linear in the concentrations ranging from 10 to 200 µg/kg. Mean extraction recoveries of enrofloxacin and ciprofloxacin were in the  range of 70-88 %. The limits of quantification for enrofloxacin and ciprofloxacin were 36 and 30 µg/kg, respectively. This RP-HPLC  method has highly applicability for routine analysis of residual fluoroquinolones in buffalo meat below Codex MRL.
Keywords: Residues; Enrofloxacin; Ciprofloxacin; Buffalo meat; HPLC method